Screening for Learning Disability among Adolescents Using Child Adolescent Psychiatric Screening (CAPS) Tool - R S, Dr. Nisha; S, Dr. Soumya.; Thumbayil, Dr. Nayana K (International Journal of Innovative Research in Medical Science, 2017)
Learning disability is a very common developmental disorder that we encounter in school age children. A cross sectional study was conducted in a government school of Pathanamthitta district. The study population was adolescent students belonging to the age group of 12 -18 years. Children and their parents who gave consent and were present on the day of data collection were included in this study. Total 273 children and parents were screened. Screening was done using Child Adolescent Psychiatric Screening (CAPS) tool. Out of the total 273 subjects, 72 % of students were in the age group of 15-18years. The prevalence of symptoms suggestive of learning disability in the study subjects was 31.14%. Among this, 28.2 % had mild, 2.19 % had moderate and 0.73% had severe symptom complex suggestive of learning disability. According to the parents, prevalence of symptom wise learning disability was 13.6% (mild12.08%, moderate 1.46% and severe none). Total prevalence of symptom complex group of learning disability as per children is 31.14% and as per parents is 13.6%. Girls showed an increased prevalence compared to boys. The present study focus on importance of early detection of learning disability in children and their parent’s awareness.